Impact of Environmental Management Accounting Practices on Financial Performance of Listed Manufacturing Companies in Sri Lanka. - Larojan, C.; Janaki, S.T. (University of Ruhuna, Sri Lanka, 2014)
The aim of this research paper is to examine the Environmental Management Accounting (EMA) practices in achieving financial performances in listed manufacturing companies in Colombo Stock Exchange (CSE). This is an exploratory study based on analyzing primary and secondary data to answer the research problem of how does the application of EMA relate with financial performance in the listed manufacturing companies in Sri Lanka. Literatures bordering on the areas of EMA practices were reviewed. A well-designed structured questionnaire was used to collect the primary data. EMA application is employed as independent variable and parameters were used to measure the independent variables such as environmental information, environmental evaluation, environmental cost savings and environmental laws whereas financial performance is the dependent variable profitability and revenue growth were used to measure the dependent variable. Top level, middle level and lower level of managers of the 39 manufacturing companies which are listed in CSE have been sampled. Correlations and multiple regression analysis have been used to analyze the data. Results reveal that there is a statistically significant positive relationship between practices of EMA and financial performance. The results of this study provide directions towards building a strong knowledge base for future EMA development. The results suggest that government should establish legal and regulatory framework for environmental issues. This research paper makes an original contribution to the growing body of empirical studies on practices of EMA in Sri Lanka.
Keywords: Colombo stock exchange.; Environmental management accounting; Financial performance.; Listed manufacturing companies